Developing Problem-Based Learning (PBL) Worksheets for the Eight Grade Students at Junior High School - Isrokijah, Isrokijah (LLT Journal: A Journal on Language and Language Teaching, 2015)
This study aims at developing problem-based learning (PBL) worksheets for the eighth grade students at junior high school. It belongs to Borg Galls research and development R D, involving 35 students from one class as the subjects. Interview guide for the teachers and questionnaire for the students were employed to collect data in needs analysis, and checklist in validation and try-out stages. The qualitative data collected through interview was analyzed descriptively, while, the quantitative data collected through questionnaire and checklist was analyzed using statistic descriptive by counting the frequency of appearance of the response. Finally the result of the data analysis was synthesized to get the real picture about the teachers and students response towards the use of PBL worksheets in learning English.